2017
DOI: 10.1021/acs.energyfuels.6b02975
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metallic Heating Plates on Coal Pyrolysis Behavior in a Fixed-Bed Reactor Enhanced with Internals

Abstract: A newly configured fixed-bed reactor with internals has been proposed to enhance the coal pyrolysis performance. In this study, the effects of metallic plates on coal pyrolysis behavior were investigated in this reactor. The results show that the increased quantity of the metallic plates enhanced the heat transfer and shortened the residence time of volatiles within the coal particles. In addition, the pressure drop results suggest that the increased quantity of plates caused short circuiting of gas and raised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…The BMS helps the operator prevent maloperation during the fuel preparation and the start and stop of the combustion equipment to prevent possible damage to the fuel preparation system and the combustion equipment. It monitors the fuel status, ignition gas and primary flame status to ensure proper purging and ignition procedures are performed [2]. When the heating furnace runs abnormally, the DCS system first alarms and the operator should make adjustments in time to make the alarm parameters return to average values.…”
Section: Interlocking Protection Of Heating Furnace Devicementioning
confidence: 99%
“…The BMS helps the operator prevent maloperation during the fuel preparation and the start and stop of the combustion equipment to prevent possible damage to the fuel preparation system and the combustion equipment. It monitors the fuel status, ignition gas and primary flame status to ensure proper purging and ignition procedures are performed [2]. When the heating furnace runs abnormally, the DCS system first alarms and the operator should make adjustments in time to make the alarm parameters return to average values.…”
Section: Interlocking Protection Of Heating Furnace Devicementioning
confidence: 99%
“…Pyrolysis, which is defined as the rapid decomposition of organic materials in the absence of oxygen, is a promising thermal approach that can be used to convert biomass into energy and chemical materials, especially in China. Biomass pyrolysis poly-generation technology employs modern biomass carbonization technology at its core, with biochar, pyrolysis gas, and pyrolysis oil as key coproducts. , Thermochemical conversion of agricultural wastes has a unique ability to address the food, water, and energy nexus. , Biochar has multiple uses, e.g., as solid fuel, an adsorbent material, a soil amendment, and a component of slow release fertilizer, thereby helping to address many challenges in sustainable food production, environmental contamination, and climate change mitigation, as well as adaptation. Pyrolysis gas is a clean fuel that can be used for heating and cooking applications . The liquid coproducts of biomass pyrolysis can be used as fuel or source of chemicals, such as phenols and organic acids. , A recent survey of crop straw resources in China showed that the theoretical resource of major crop (corn, wheat, rice, cotton, et al) straw in 2015 was ∼1.04 billion tons (see Table ) and the collectible resource was as much as 900 million…”
Section: Introductionmentioning
confidence: 99%